Concurrent pyoderma gangrenosum and infection with Scedosporium apiospermum. (28th April 2015) - Tilakaratne, Dev; Ryan, Emma; Pearce, Annette
Abstract: We present a patient with pyoderma gangrenosum (PG) following hip surgery, who developed an exacerbation of her ulceration in conjunction with new areas on her lower limbs. Clinically, features of PG and deep fungal infection were apparent. S cedosporium apiospermum was isolated from the ulcers.